Intertidal community responses to field‐based experimental warming. Issue 7 (27th November 2014) - Kordas, Rebecca L.; Dudgeon, Steve; Storey, Stefan; Harley, Christopher D. G.
<x xml:space="preserve">Abstract</x> As the climate warms, there is little doubt that ecosystems of the future will look different from those we see today. However, community responses to warming in the field are poorly understood. We examined the effects of field‐based warming on intertidal communities in the Salish Sea, which is a regional thermal 'hot spot' and therefore a model system for studying thermally stressed communities. We manipulated temperature at three tidal heights by deploying black‐ and white‐bordered settlement plates. Black plates increased in situ substratum temperature by an average of 2.6°C (maximum temperature, 40.9°C). Barnacles fared poorly on black plates in all zones. When overall thermal stress was highest (summer in the high intertidal zone) herbivores were absent. In lower tidal zones, herbivores were abundant on white plates but were scarce on black plates. The total percent cover of algae was unaffected by the temperature treatment, despite the fact that macroalgae were expected to be the least thermally tolerant functional group. However, we did find that ephemeral green algae exhibited a delay in phenology on black plates. We also found that species richness declined and invertebrate assemblage structure was altered due to warming. Results from this year long experiment suggest that communities in thermally stressful habitats respond to warming via the interplay between species‐specific thermal responses and secondary adaptive strategies such as behavioral microhabitat selection. Declines in diversity and changes in the invertebrate assemblage were due to the decline of local thermally‐stressed species and the lack of replacement by warm‐adapted species. Given the low variation in the species pool along the northeast Pacific coastline, the arrival of warm‐adapted species to the Salish Sea may not occur over relevant time scales, leaving local communities depauperate.